Modern Solar Facilities : Advanced Solar Science, Proceedings of a Workshop held at Göttingen, September 27-29, 2006 - Wittman, Axel D.; Puschmann, Klaus G.; Kneer, Franz (Book collections on Project MUSE., 2010)
An international workshop entitled: "Modern Solar Facilities - Advanced Solar Science" was held in Göttingen from 27 to 29 September, 2006. It took place in the new physics building located in the northern campus of the Georg-August-Universität. The workshop was attended by 88 participants from 24 different countries (see the list of participants, pp. 375-381, containing the institutional addresses at the time of the workshop). With 11 invited talks, 28 contributed talks, and 44 poster contributions the workshop gathered leading researchers in the field and gave a broad overview of the current state of solar research.